19. REPRESENTATIONS OF ISLAM AND MUSLIMS IN THE CORPUS OF CONTEMPORARY AMERICAN ENGLISH (COCA - Rashid Ali, Farrah Diebaa; Mohd Zuki, Anis Zulaikha; Badaruddin, Zuraidar (Journal of Islamic, Social, Economics and Development, 2024)
How a person, group, culture, or concept is portrayed significantly impacts how the world perceives and holds ideas. Many communication channels, nevertheless, may be perceived as prejudiced in favor of particular communities that belong to distinct racial and religious groups. The Muslim communities who practice Islam and the religion itself are sometimes misinterpreted and poorly portrayed in Western media. Thus, this study aims to examine the representations of Muslims and Islam through a collocational analysis of the word Muslim and Islam in the Corpus of Contemporary American English (COCA). Two sets of collocation were compared; one was from 2000-2004, around the September 11, 2001 incident, and the other after the introduction of Trump’s policy on Muslim banning in 2015-2019. The purpose of comparing these two was to examine how Islam and Muslims were represented and described during the two events. A total of 132 collocations for the words Islam and Muslim were identified in the four distinct genres: spoken, academic, newspaper, and magazine. The analysis was guided by Johnston's (2024) Indexicality and Haider's (2016) Collocational analysis frameworks. The results show that prejudices toward Islam and Muslims go beyond rhetoric and linguistic analysis, proving that a collocational analysis is a potent instrument to reveal social realities, representations, and prejudices a community holds against a particular group during a specific period.